What attributes of extra virgin olive oil are really important for consumers: a meta-analysis of consumers' stated preferences - Teresa Del Giudice; Carla Cavallo; Francesco Caracciolo; Gianni Cicia (Agricultural and Food Economics, 2015)
The literature on food economics has extensively analyzed consumer preferences for extra-virgin olive oil attributes. In order to summarize and systematize the information gained in recent years, it seems appropriate to make a critique of the existing literature. First, we carry out a narrative systematic review of the literature on the topic. Subsequently, using only the empirical contributions which provide estimates of consumer willingness to pay for quality attributes including a measure of the goodness of the estimation (20 papers with 78 estimates), a meta-analysis was conducted to synthesize the empirical results obtained.
Keywords: D12; C25; Q18; 330; Meta-analysis; Consumers preferences; Extra-virgin olive oil